The effects of nasal continuous positive airway pressure on cardiac function in premature infants with minimal lung disease: a crossover randomized trial - Beker, Friederike; Rogerson, Sheryle R.; Hooper, Stuart B.; Wong, Connie; Davis, Peter G. (The journal of pediatrics, 2014)
Objective - To assess the effects of different nasal continuous positive airway pressure (nCPAP) pressures on cardiac performance in preterm infants with minimal lung disease, we conducted a randomized, blinded crossover study. - Study design - We studied infants between 28 and 34 weeks' corrected gestational age, treated with nCPAP of 5 cm H2O, in air. Infants with significant cardiac shunts were excluded. Infants were randomly assigned to nCPAP levels of 4, 6, and 8 cm H2O for 15 minutes each. Right and left ventricular outputs and left pulmonary artery and superior vena cava flows were measured 15 minutes after each change. - Results - Thirty-four infants born at a mean gestational age of 29 weeks with a birth weight of 1.3 kg were studied. There were no significant differences in right and left ventricular outputs and left pulmonary artery and superior vena cava flows at different levels of nCPAP. - Conclusion - We investigated the effect of increasing nCPAP levels on cardiac output. We conclude that nCPAP levels between 4 and 8 cm H2O did not have an effect on cardiac output in stable preterm infants with minimal lung disease.
Available online 15 December 2013
Gesehen am 20.11.2020
Portions of this study were presented as a oral presentation at the annual meeting of the Perinatal Society of Australia and New Zealand, April 14-17, 2013 in Adelaide, Australia, and as a poster at the Pediatric Academic Societies' meeting, May 4-7, 2013 in Washington, DC
Portions of this study were presented as a oral presentation at the annual meeting of the Perinatal Society of Australia and New Zealand, April 14-17, 2013 in Adelaide, Australia, and as a poster at the Pediatric Academic Societies' meeting, May 4-7, 2013 in Washington, DC